Burning mouth syndrome and oral microbiota: a review - Russo, Michele; Crafa, Pellegrino; Franzoni, Lorella; Franceschi, Marilisa; Rodriguez-Castro, Kryssia Isabel; Tursi, Antonio; Brandimarte, Giovanni; Di Mario, Francesco (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Burning mouth syndrome (BMS) is a chronic condition characterized by intraoral burning or dysesthetic sensations without evident causative lesions. The etiology of BMS remains unclear, and effective treatments are lacking. This review aimed to evaluate the correlation between BMS and oral microbiota by analyzing relevant studies. Methods: A literature search was conducted in PubMed, Embase, and Scopus databases from inception until 11 june 2023. Results: Two studies were identified, providing preliminary evidence on this association. The first study compared the oral microbial profiles of patients with primary BMS and healthy controls, revealing lower microbial diversity in the BMS group and specific microbial taxa associated with BMS. The second study assessed the incidence of oral infections in BMS patients and their impact on symptoms, finding no significant correlation between oral infections and BMS symptoms. Conclusions: The findings suggest a potential association between oral microbiota and BMS, with alterations in the oral microbial community possibly contributing to BMS pathogenesis. Disease-specific microbial markers may have diagnostic implications for BMS. However, the limited number of studies and heterogeneity among them emphasize the need for further well-designed research employing larger sample sizes, standardized methodologies, and consistent diagnostic criteria.